SYMPTOM PROFILE OF SUBSTANCE INDUCED PSYCHOSIS VERSUS PSYCHOSIS WITH COMORBID SUBSTANCE AT KUWAIT ADDICTION TREATMENT CENTER - Sameh Mohamed Yousri Bondok; Marwa Mohsen Ramadan; Hossam Ahmed Ali; Najla Homoud Al- Ayyadhi (Scholar Express Journals, 2022)
The determination of possible indicators of the abnormalities could facilitate their detection and management because the differential diagnosis of substance-induced psychotic disorder and psychosis with comorbid substance is especially difficult while in a severe admittance when psychotic symptoms are at their worst. The article compares individuals with substance-induced psychosis and individuals with psychosis and concomitant drug to examine the phenomenological elements and many factors affecting the clinical picture
Keywords: Substance use disorder; Dual diagnosis; Psychosis with comorbid substance use; psychosis